Low-concentration electrolyte containing non-corrosive organic halide and application of low-concentration electrolyte in zinc-iodine battery

By using low-concentrated electrolyte containing non-corrosive organic halides in zinc-iodine batteries, the I0/I+ redox pair is activated, and the corrosion and kinetic problems of zinc negative electrode caused by traditional electrolytes are solved, and the performance of zinc-iodine batteries with high energy density, high power density and long life is achieved.

CN119725797AActive Publication Date: 2025-03-28GUANGDONG UNIV OF TECH

Patent Information

Application Number
CN202411821594.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-28
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

During the excitation process of high voltage I0/I+ redox, the high concentration of halogen ions of the electrolyte lead to high viscosity, low ion conductivity, and strong corrosiveness, resulting in rapid dissolution of the zinc negative electrode, limiting the practicalization of the four-electron iodine-converted zinc iodine batteries.

Method used

A low-concentrated electrolyte containing non-corrosive organic halides is used to activate the I0/I+ redox pair through the C-Br bond, forming a C-Br-I chemical bond, excite and stabilize the I0/I+ redox pair, avoiding the corrosiveness and kinetic problems of high-concentrated halogen ions.

Benefits of technology

The four-electron iodine conversion zinc-iodine battery has been realized to maintain the capacity contribution of I0/I+ redox pairs under high current density, and obtain high specific energy, high specific power and long-life battery performance, while reducing the corrosion and cost of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725797A_ABST
    Figure CN119725797A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and discloses a low-concentration electrolyte containing a non-corrosive organic halide and an application of the low-concentration electrolyte in a zinc-iodine battery. The electrolyte comprises zinc sulfate, deionized water and organic halide, the molar ratio of zinc sulfate to organic halide is 3: (0.3-1); and the organic halide is one or more of 2-bromoacetamide, 2-bromopropionamide or 3-bromopropionamide. The organic halide can activate an I0 / I < + > redox pair to form a novel organic interhalogen chemical bond (C-Br-I) which is different from a previous I-Br bond and is faster in dynamics, and hydrolysis and shuttling of an organic interhalogen compound are remarkably inhibited under a low-concentration condition. According to the invention, the problems of high cost and zinc negative electrode point corrosion caused by the conventional high-concentration halogen ion electrolyte and iodine conversion kinetics hysteresis caused by the thick electrolyte are avoided, the energy density, the power density and the cycle life of the four-electron iodine conversion type zinc-iodine battery are also remarkably improved, and the four-electron iodine conversion type zinc-iodine battery has good practicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a low-concentration electrolyte containing non-corrosive organic halides and application thereof in zinc-iodine batteries. Background Art

[0002] Large-scale grid-connected utilization of renewable energy is a key link in achieving the goal of carbon neutrality. Compared with the currently widely used pumped storage technology, the flexibility of electrochemical energy storage in time and space can better meet the intermittent characteristics of renewable energy generation, and plays a vital role in large-scale energy storage applications. At present, commercial organic system lithium-ion batteries still dominate large-scale electrochemical energy storage. However, the limited reserves of lithium resources and the safety issues caused by the use of flammable organic electrolytes have increasingly exposed its limitations in large-scale energy storage applications.

[0003] Low-cost, high-safety aqueous zinc batteries are a new type of electrochemical energy storage technology that has emerged in recent years and are expected to be used in large-scale energy storage applications. However, the traditional insertion and extraction positive electrodes (manganese and vanadium oxides) have low voltages (below 1.4V) and low capacities (less than 300mAh g -1 ), resulting in the battery energy density being less than ideal overall (100Wh kg -1 In contrast, the use of a valence-variable iodine conversion positive electrode can simultaneously achieve high battery capacity and high energy density. In particular, when I - / I 0 and I 0 / I + When both redox pairs are excited, a four-electron transfer process can be achieved, and up to 422.2 mAh g -1 The specific capacity and 420Wh kg -1 energy density. In this process, the high voltage I 0 / I + The redox couple contributes more than half of the capacity and energy density. - / I 0 Based on the redox pair, the excitation I 0 / I + Redox pairs have very important practical value.

[0004] In previous studies, high-valence I 0 / I + Redox couple activation usually requires the presence of high concentrations of halogen ions (Br - , Cl - ) electrolyte. Although this type of electrolyte can stimulate and stabilize I +, but their high viscosity and low ionic conductivity significantly affect the battery reaction kinetics. In particular, these electrolytes are often extremely corrosive, causing the zinc negative electrode to quickly dissolve due to severe pitting corrosion. These factors have seriously hindered the practical application of four-electron iodine conversion zinc-iodine batteries. Summary of the invention

[0005] Based on the problems existing in the above background technology, the present invention provides a low-concentration electrolyte containing non-corrosive organic halides, which activates I by means of C-Br bonds in additives. 0 / I + Redox pairs form C-Br-I chemical bonds, which stimulate and stabilize I 0 / I + The effect of redox couple enables the battery to maintain I for a long time at high current density. 0 / I + The capacity contribution of the redox couple is improved, thereby obtaining a zinc-iodine battery with high specific energy, high specific power and long life.

[0006] Another object of the present invention is to provide a method for preparing the above-mentioned low-concentration electrolyte containing non-corrosive organic halides.

[0007] Another object of the present invention is to provide a four-electron iodine conversion zinc-iodine battery assembled based on the above-mentioned low-concentration electrolyte containing organic halides, wherein the positive electrode can excite reversible I - / I 0 and I 0 / I + Redox couple.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A low-concentration electrolyte containing non-corrosive organic halides comprises zinc sulfate, deionized water and organic halides; the molar ratio of the zinc sulfate to the organic halides is 3:(0.3-1); the organic halides are one or more of 2-bromoacetamide, 2-bromopropionamide or 3-bromopropionamide.

[0010] Preferably, the concentration of the electrolyte is greater than 0 and less than or equal to 5 mol / L.

[0011] The method for preparing the low-concentration electrolyte containing non-corrosive halides comprises the following specific steps:

[0012] S1. Add zinc sulfate to deionized water and stir at room temperature to obtain a zinc sulfate solution;

[0013] S2. Add an organic halide to a zinc sulfate solution and stir at room temperature to prepare a low-concentration electrolyte containing a non-corrosive organic halide.

[0014] Preferably, the stirring time in step S1 is 1 to 2 hours, and the stirring time in step S2 is 2 to 4 hours.

[0015] A four-electron iodine conversion type zinc-iodine battery comprises a positive electrode, a negative electrode, a diaphragm and a low-concentration electrolyte containing a non-corrosive organic halide.

[0016] Preferably, the positive electrode is an iodine composite material encapsulated by activated carbon, the negative electrode is a zinc metal sheet, and the separator is glass fiber.

[0017] Preferably, the activated carbon-encapsulated iodine composite material is activated carbon and iodine element supported thereon.

[0018] The present invention is the first to use a low-concentration zinc sulfate electrolyte (0-5 mol / L) containing a non-corrosive organic halide additive (2-bromoacetamide, 2-bromopropionamide or 3-bromopropionamide) to replace the previous high-concentration halogen ion electrolyte (15-30 mol / L). The electrolyte does not contain highly corrosive free halogen ions (Br - or Cl - ), which stimulates I 0 / I + The redox couple relies on the formation of C-Br-I chemical bonds instead of conventional IX (X = Br, Cl) interhalogen compounds. Compared with conventional interhalogen chemical bonds, C-Br-I chemical bonds have faster kinetics and are less prone to hydrolysis and shuttle effects. Therefore, the assembled four-electron zinc-iodine battery can simultaneously achieve high energy density, high power density and long cycle life, providing a new solution for the development of four-electron iodine conversion zinc-iodine batteries.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. This invention is the first in the industry to propose the use of organic halogen chemical bonds (C-Br-I) to stimulate high voltage I 0 / I + Redox pairs, and with conventional I - / I 0 The redox pair combines to form a high-capacity four-electron iodine conversion zinc-iodine battery. 0 / I + Redox couple, dependent on I excited by C-Br-I 0 / I + The redox couple has faster reaction kinetics, and the formed organohalogen intermetallic compounds are less susceptible to hydrolysis and shuttling effects in low-concentration electrolytes.

[0021] 2. The low-concentration electrolyte containing non-corrosive organic halides of the present invention has lower cost, lower corrosiveness, and higher ion conductivity than the previous aqueous electrolyte containing high-concentration halogen ions, and avoids the serious pitting corrosion of the zinc negative electrode by the high-concentration halogen ion aqueous electrolyte, which leads to its rapid digestion.

[0022] 3. The present invention optimizes the ratio of zinc sulfate and organic halide additives in the electrolyte to achieve a four-electron iodine conversion zinc-iodine battery at an ultra-large rate (60Ag -1 ) under fast charge conditions, significantly improving the energy density and energy efficiency of the four-electron iodine conversion zinc-iodine battery; -1 Under high current density, a long life of more than 16,000 times can be achieved, which is conducive to reducing the cost of battery use; the optimized electrolyte can support a high loading capacity (24 mg cm) far exceeding that currently reported in the industry. -2 ) The iodine positive electrode realizes four-electron conversion, and I 0 / I + The high-voltage discharge platform capacity contributed by the redox pair can be maintained at around 48%, which helps to obtain high-energy single cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The relationship between the viscosity and ion conductivity of the high-concentration salt electrolyte reported in the current industry and the concentration of Comparative Example 3 and Example 1;

[0024] Figure 2 It is a cost comparison chart of Comparative Example 1, Comparative Example 3, Examples 1-3 and a high-concentration salt electrolyte system (10 mol / L or more);

[0025] Figure 3 Tafel curves of zinc negative electrode in different electrolytes;

[0026] Figure 4 High-definition digital photos of battery shells and zinc sheets after 500 cycles of zinc-iodine batteries assembled using the electrolytes in Application Example 1 and Comparative Examples 1 and 3;

[0027] Figure 5 The cycling performance of Zn / / Zn symmetrical cells assembled using the three electrolytes in Comparative Examples 1, 3 and Example 1;

[0028] Figure 6 Cyclic voltammetry curves of zinc-iodine batteries assembled using the electrolytes in Comparative Examples 1-3 and Application Examples 1-3;

[0029] Figure 7 The charge transfer activation energy of zinc-iodine batteries assembled using the electrolytes in Application Example 1 and Comparative Example 3 respectively;

[0030] Figure 8High-definition digital photos of zinc-iodine batteries assembled with the electrolytes in Application Example 1 and Comparative Example 3 after one cycle of charge and discharge in a beaker battery;

[0031] Fig. 9 The rate performance of zinc-iodine batteries assembled using the electrolytes in Application Example 1 and Comparative Example 3;

[0032] Fig.10 The charge and discharge curves of zinc-iodine batteries assembled with the electrolytes in Application Example 1 and Comparative Example 3 at different currents;

[0033] Fig.11 The zinc-iodine battery was assembled using the electrolytes in Application Example 1 and Comparative Examples 1 and 3 at 2A g -1 Cycling performance under current density;

[0034] Fig.12 To assemble a zinc-iodine battery using the electrolyte in Application Example 1 at 20Ag -1 and 40Ag -1 Cycling performance under current density;

[0035] Fig.13 To evaluate the rate performance of zinc-iodine batteries assembled with the electrolyte in Application Example 1 under different iodine loadings;

[0036] Fig.14 The charge and discharge curves of the zinc-iodine battery assembled with the electrolyte in Application Example 1 under high iodine load;

[0037] Fig.15 The zinc-iodine battery assembled with the electrolytes in Application Example 1 and Comparative Example 3 was tested at high iodine loading (14.65 mg cm -2 ) under the cycle performance;

[0038] Fig.16 This is a comparison of the iodine positive electrode loading of the zinc-iodine battery assembled using application example 1 and the high-concentration salt electrolyte currently used in the industry. DETAILED DESCRIPTION

[0039] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0040] Example 1

[0041] 1. Add 0.863 g zinc sulfate to 1 mL deionized water and stir at room temperature for 2 h to prepare a 3 mol / L zinc sulfate solution;

[0042] 2. Add 0.097 g of 2-bromoacetamide to the above zinc sulfate solution and stir at room temperature for 2 to 4 hours to obtain an aqueous electrolyte containing 2-bromoacetamide, wherein the concentration of 2-bromoacetamide is 0.7 mol / L.

[0043] Example 2

[0044] 1. Add 0.863 g zinc sulfate to 1 mL deionized water and stir at room temperature for 2 h to prepare a 3 mol / L zinc sulfate solution;

[0045] 2. Add 0.106 g of 2-bromopropionamide to the above zinc sulfate solution, stir at room temperature for 2 to 4 hours, take the supernatant, and prepare an aqueous low-concentration electrolyte containing 2-bromopropionamide, wherein the concentration of 2-bromoacetamide is 0.7 mol / L.

[0046] Example 3

[0047] 1. Add 0.863 g zinc sulfate to 1 mL deionized water and stir at room temperature for 2 h to prepare a 3 mol / L zinc sulfate solution;

[0048] 2. Add 0.106 g of 3-bromopropionamide to the above zinc sulfate solution, stir at room temperature for 2 to 4 hours, take the supernatant, and prepare an aqueous low-concentration electrolyte containing 3-bromopropionamide, wherein the concentration of 3-bromopropionamide is 0.7 mol / L.

[0049] Comparative Example 1

[0050] 1. Add 0.863 g zinc sulfate to 1 mL deionized water and stir at room temperature for 2 h to prepare a 3 mol / L zinc sulfate solution.

[0051] 2. At room temperature, the supercapacitor activated carbon encapsulated iodine composite material (I@AC), acetylene black (Super P) conductive additive and sodium carboxymethyl cellulose binder (CMC aqueous solution) with a mass ratio of 8:1:1 were ground and fully mixed to form a slurry, which was coated on the carbon cloth current collector and then dried to obtain the I@AC electrode.

[0052] 3. Use the obtained zinc sulfate solution as electrolyte, I@AC pole piece as positive electrode, and metal zinc sheet as negative electrode to assemble zinc iodine battery, abbreviated as ZSO.

[0053] Comparative Example 2

[0054] 1. Add 0.863 g zinc sulfate to 1 mL deionized water and stir at room temperature for 2 h to prepare a 3 mol / L zinc sulfate solution.

[0055] 2. Add 0.041 g of acetamide to the above zinc sulfate solution and stir at room temperature for 2 to 4 hours to prepare an aqueous low-concentration electrolyte containing 0.7 mol / L acetamide.

[0056] 3. At room temperature, I@AC, Super P and CMC aqueous solution with a mass ratio of 8:1:1 were ground and fully mixed to form a slurry, which was then coated on a carbon cloth current collector and then dried to obtain an I@AC pole piece.

[0057] 4. The obtained aqueous low-concentration electrolyte containing acetamide was used as the electrolyte, the I@AC electrode was used as the positive electrode, and the metal zinc sheet was used as the negative electrode to assemble a zinc-iodine battery, which was abbreviated as Ace. Comparative Example 2 does not contain halogen and cannot activate the four-electron reaction, eliminating the interference of the amide group.

[0058] Comparative Example 3

[0059] 1. Add 0.863 g zinc sulfate to 1 mL deionized water and stir at room temperature for 2 h to prepare a 3 mol / L zinc sulfate solution;

[0060] 2. Add 0.079 g zinc bromide to the above zinc sulfate solution and stir at room temperature for 2 to 4 hours to prepare an aqueous low-concentration electrolyte containing 0.7 mol / L zinc bromide.

[0061] 3. At room temperature, I@AC, Super P and CMC aqueous solution with a mass ratio of 8:1:1 were ground and fully mixed to form a slurry, which was then coated on a carbon cloth current collector and then dried to obtain an I@AC pole piece.

[0062] 4. Using the obtained low-concentration aqueous electrolyte containing zinc bromide as the electrolyte, the I@AC electrode as the positive electrode, and the metal zinc sheet as the negative electrode, a zinc-iodine battery is assembled, abbreviated as ZnBr2.

[0063] Application Example 1

[0064] 1. Grind activated carbon and iodine powder in a mass ratio of 1:1 to obtain an I@AC composite material.

[0065] 2. At room temperature, I@AC, Super P and CMC aqueous solution with a mass ratio of 8:1:1 were ground and mixed thoroughly to form a slurry, which was then coated on a carbon cloth current collector and then dried to obtain an I@AC pole piece;

[0066] 3. At room temperature, a zinc-iodine battery was assembled using the aqueous low-concentration electrolyte containing organic halides obtained in Example 1 as the electrolyte, the I@AC electrode as the positive electrode, and the metal zinc sheet as the negative electrode, abbreviated as BrAce.

[0067] Application Example 2

[0068] 1. Grind activated carbon and iodine powder in a mass ratio of 1:1 to obtain an I@AC composite material.

[0069] 2. At room temperature, I@AC, Super P and CMC aqueous solution with a mass ratio of 8:1:1 were ground and mixed thoroughly to form a slurry, which was then coated on a carbon cloth current collector and then dried to obtain an I@AC pole piece;

[0070] 3. At room temperature, a zinc-iodine battery was assembled using the aqueous low-concentration electrolyte containing an organic halide additive obtained in Example 2 as the electrolyte, the I@AC electrode as the positive electrode, and the metal zinc sheet as the negative electrode, which was abbreviated as 2-BrPace.

[0071] Application Example 3

[0072] 1. Grind activated carbon and iodine powder in a mass ratio of 1:1 to obtain an I@AC composite material.

[0073] 2. At room temperature, I@AC, Super P and CMC aqueous solution with a mass ratio of 8:1:1 were ground and mixed thoroughly to form a slurry, which was then coated on a carbon cloth current collector and then dried to obtain an I@AC pole piece;

[0074] 3. At room temperature, a zinc-iodine battery was assembled using the aqueous low-concentration electrolyte containing the organic halide additive obtained in Example 3 as the electrolyte, the I@AC electrode as the positive electrode, and the metal zinc sheet as the negative electrode, which was abbreviated as 3-BrPace.

[0075] Figure 1 The relationship between the viscosity and ion conductivity of high-concentration salt electrolyte reported in Example 1, Comparative Example 3 and the concentration in the current industry is shown in FIG. Figure 1 It can be seen that the aqueous electrolyte containing 2-bromoacetamide in Example 1 has low viscosity and high ion conductivity, and has good application prospects. Figure 2 The cost comparison chart of Comparative Examples 1 and 3 and Examples 1-3 and the high-concentration salt electrolyte system is shown in FIG. Figure 2 It can be seen that compared with the traditional high-concentration salt electrolyte, Example 1 has lower cost and has good commercial prospects.

[0076] Figure 3 The Tafel curves of zinc anode in different electrolytes are shown in Figure 1. The scan rate is 1 mV s -1 .Depend on Figure 3 It can be seen that compared with Comparative Examples 1 and 3, the corrosion potential of the zinc negative electrode in Example 1 is more positive and the corrosion current is smaller, indicating that the low-concentration aqueous electrolyte containing non-corrosive organic halide additives is more conducive to reducing the corrosion of the zinc negative electrode. Figure 4 This is a high-definition digital photo of the zinc sheet negative electrode after 500 electrochemical cycles of the zinc-iodine battery assembled in Application Example 1 and Comparative Example 3. Figure 4It can be seen that the zinc sheet of comparative example 3 has extremely serious pitting corrosion and has been perforated, while the zinc sheet of application example 1 is relatively intact, indicating that the use of a low-concentration electrolyte containing a non-corrosive organic halide additive avoids the conventional free Br - Effect of aqueous electrolyte on pitting corrosion of zinc sheet negative electrode.

[0077] Figure 5 The cycling performance of the Zn / / Zn symmetric battery assembled using the three electrolytes in Comparative Examples 1 and 3 and Example 1, the surface current density and surface capacity are 5 mA cm -2 and 1mAh cm -2 .Depend on Figure 5 It can be seen that compared with Comparative Examples 1 and 3, the Zn / / Zn symmetric battery using the non-corrosive low-concentration electrolyte in Example 1 exhibits lower polarization and longer cycle life. Figure 6 For Application Examples 1-3 and Comparative Examples 1-3 at 1mV s -1 Cyclic voltammetry curve at the scan rate. Figure 6 It can be seen that both Comparative Example 3 and Application Examples 1-3 have the corresponding 0 / I + The redox peak of the conversion was not found in Comparative Examples 1-2, indicating that the free Br - Both organic bromides can activate I 0 / I + Compared with Comparative Example 3, the corresponding I in Application Example 1 0 / I + The redox peak current of the conversion is higher, and there is no Br2 precipitation, which means that organic bromide is more conducive to the excitation of I 0 / I + conversion, and the electrochemical stability of the additive itself within the same voltage window can be guaranteed.

[0078] Figure 7 is the charge transfer activation energy of the zinc-iodine battery assembled with the electrolyte in Application Example 1 and Comparative Example 3. The charge transfer activation energy of Comparative Example 3 and Application Example 1 was calculated using the Arrhenius equation. Figure 7 It can be seen that compared with Comparative Example 3, the charge transfer activation energy of Application Example 1 is lower and the kinetics is faster. Figure 8 This is a digital photo of the zinc-iodine battery assembled with the electrolyte in Application Example 1 and Comparative Example 3 after one cycle of charge and discharge in a beaker battery. Figure 8 It can be seen that compared with Comparative Example 3, the electrolyte in Application Example 1 has no obvious color change, indicating that the organic halide additive can effectively inhibit the shuttling of charge and discharge active products.

[0079] Fig. 9 The rate performance of the zinc-iodine battery assembled with the electrolyte in Application Example 1 and Comparative Example 3. Fig. 9It can be seen that the rate performance of Application Example 1 is much better than that of Comparative Example 3. -1 At current densities of 1.3, 1.7, 2.1, 3.3, 4.6, 5.9, 7.9, 8.3, 9.9, 10.1, 11.3, 12.9, 13.7, 14.9, 16.7, 18.3, 19.9, 21.3, 22.1, and 18.0 mAh g -1 . Fig.10 The charge and discharge curves of the zinc-iodine battery assembled with the electrolytes in Application Example 1 and Comparative Example 3 at different current densities. Fig.10 It can be seen that even at 60Ag -1 Under the ultra-large current density, the stimulating effect of the organic halide additive on iodine conversion in Application Example 1 can still be maintained.

[0080] Fig.11 The zinc-iodine battery assembled with the electrolyte in Application Example 1 and Comparative Examples 1 and 3 is 2Ag -1 Cycling performance diagram under current density. Fig.11 It can be seen that the capacity retention rate of Application Example 1 after 2000 cycles is as high as 90%, while the capacity retention rate of Comparative Example 3 after 2000 cycles is only 50.3%. This shows that the cycle stability of Application Example 1 is much better than that of Comparative Example 3. Fig.12 The zinc-iodine battery assembled with the electrolyte in Application Example 1 is 20Ag -1 and 40Ag -1 Cycling performance under current density. Fig.12 It can be seen that in application example 1, at 20Ag -1 and 40A g -1 Under high current density, it can stably cycle for more than 8000 and 16000 cycles respectively.

[0081] Fig.13 The figure is the rate performance diagram of the zinc-iodine battery assembled with the electrolyte in Application Example 1 at different iodine loadings. Fig.13 It can be seen that in Application Example 1, even at 24 mg cm -2 It still has excellent rate performance under high iodine loading, showing good application prospects. Fig.14 The charge and discharge curves of the zinc-iodine battery assembled with the electrolyte in Application Example 1 under high iodine loading. It can be seen that even at 9.8 mg cm -2 Under high iodine loading, Application Example 1 can still maintain sufficient four-electron reversible transformation reaction. Fig.15 The zinc-iodine battery assembled with the electrolytes in Application Example 1 and Comparative Example 3 was tested at high iodine loading (14.65 mg cm -2 ) under the cycle performance diagram. Fig.15 It can be seen that the high-load battery assembled in Comparative Example 3 failed after 7 cycles of activation, while the high-load zinc-iodine battery assembled in Application Example 1 can provide up to 3.9 mAh cm -2The capacity can be cycled stably for 400 times without attenuation. Fig.16 The figure is a comparison chart of iodine loading mass compatible with Application Example 1 and high-concentration salt electrolyte system. Fig.16 It can be seen that application example 1 is as high as 24 mg cm -2 The iodine loading capacity is compatible with that of zinc-iodine batteries, far exceeding the relevant results of four-electron iodine conversion type batteries currently reported in the industry.

[0082] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A low-concentration electrolyte containing a non-corrosive organic halide, characterized in that: The electrolyte comprises zinc sulfate, deionized water and an organic halide; the molar ratio of the zinc sulfate to the organic halide is 3:(0.3-1); the organic halide is one or more of 2-bromoacetamide, 2-bromopropionamide or 3-bromopropionamide.

2. The low-concentration electrolyte containing non-corrosive halides according to claim 1, characterized in that: The concentration of the electrolyte is greater than 0 and less than or equal to 5 mol / L.

3. The method for preparing a low-concentration electrolyte containing a non-corrosive halide according to claim 1 or 2, characterized in that: The specific steps include: S1. Add zinc sulfate to deionized water and stir at room temperature to obtain a zinc sulfate solution; S2. Add an organic halide to a zinc sulfate solution and stir at room temperature to prepare a low-concentration electrolyte containing a non-corrosive organic halide.

4. The method for preparing a low-concentration electrolyte containing non-corrosive halides according to claim 3, characterized in that: The stirring time in step S1 is 1 to 2 hours, and the stirring time in step S2 is 2 to 4 hours.

5. A four-electron iodine conversion zinc-iodine battery, characterized in that: The zinc-iodine battery comprises a positive electrode, a negative electrode, a diaphragm and the low-concentration electrolyte containing non-corrosive organic halides as claimed in claim 1 or 2.

6. The four-electron iodine conversion zinc-iodine battery according to claim 5, characterized in that: The positive electrode is an iodine composite material encapsulated by activated carbon, the negative electrode is a zinc metal sheet, and the diaphragm is glass fiber.

7. The four-electron iodine conversion zinc-iodine battery according to claim 6, characterized in that: The activated carbon-encapsulated iodine composite material is activated carbon and iodine element loaded thereon.

Citation Information

Patent Citations

  • Aqueous zinc-iodine battery based on four-electron conversion reaction and electrolyte thereof

    CN111540950A

  • Electrolyte, application thereof and lithium ion battery

    CN112838273A

  • Thin metal-halogen cells

    US4226924A

Cited By

  • Positive electrode additive and electrolyte for high-stability two-electron aqueous zinc-iodine battery

    CN121507139A